Clustering of risk factors for cardiovascular disease among women in Southern Brazil: a population-based study Agregação de fatores de risco para doenças cardiovasculares em mulheres no Sul do Brasil: um estudo de base populacional - Sandra Costa Fuchs; Leila Beltrami Moreira; Susi Alves Camey; Marina Beltrami Moreira; Flávio Danni Fuchs (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2008)
The association between clustering of risk factors and self-reported cardiovascular disease among women was investigated in a cross-sectional study using a multistage population-based sample. Participants were interviewed at home about diabetes mellitus, physical activity, and diet pattern. Hypertension was defined as blood pressure > 140/90mmHg or use of anti-hypertensive medication. Cardiovascular disease included self-reported myocardial infarction, heart failure, coronary artery bypass surgery, and stroke. A sample of 1,007 women from Porto Alegre, Southern Brazil, mostly white (73%), 44.8 ± 0.8 years old, and with 9.3 ± 0.3 years of schooling was investigated. Hypertension, diabetes mellitus, obesity, low fruit and vegetable intake, and lack of vigorous or moderate physical activity were clustered into a combination of risk factors, which were independently associated with self-reported cardiovascular disease. The main cluster included hypertension and diabetes, accounting for an independent risk ratio of 8.5 (95%CI: 3.0-24.5). Clustering of cardiovascular risk factors is strongly associated with self-reported cardiovascular disease among women. A associação entre agregação de fatores de risco e doença cardiovascular auto-identificada entre mulheres foi investigada em estudo transversal, utilizando amostra de base populacional, por estágios múltiplos. Entrevista domiciliar investigou diagnóstico prévio de diabetes mellitus, atividade física e padrão alimentar. Hipertensão foi definida por pressão arterial > 140/90mmHg ou uso de anti-hipertensivo. Doença cardiovascular auto-identificada foi composta por diagnósticos prévios de infarto do miocárdio, insuficiência cardíaca e acidente vascular encefálico ou realização de cirurgia de revascularização miocárdia. Estudaram-se 1.007 mulheres de Porto Alegre, Rio Grande do Sul, Brasil, predominantemente brancas (73%), com 44,8 ± 0,8 anos e 9,3 ± 0,3 anos de escolaridade. Agregação de hipertensão, diabetes mellitus, obesidade, baixo consumo de frutas e vegetais e ausência de atividade física vigorosa ou moderada associaram-se independentemente com doença cardiovascular auto-identificada. A principal agregação foi hipertensão e diabetes com razão de prevalência = 8,5 (IC95%: 4,6-49,1). A agregação de fatores de risco cardiovascular está fortemente associada com doença cardiovascular auto-identificada entre as mulheres.